PEMBELAJARAN KEWIRAUSAHAAN: MENGUBAH ARAH, PERSEPSI, DAN SIKAP PENDALAMAN PEMAHAMAN GLOBAL DALAM RUANG LOKAL SISWA DALAM PROSES BELAJAR DI SEKOLAH TINGGI ILMU TARBIYAH RADEN WIJAYA MOJOKERTO - Munib, Munib (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
This paper is based on the fact that closeness to the real world Institutions / companies play an important role in the interactive learning process and that knowledge creation is supported by institutional manifestations of tacit knowledge that is useful for certain classes of activities. Sustainable competitiveness requires a more open replacement of resources for change, rebuilding obsolete structures and renewing economically important national or regional institutions, when imitation gradually changes capabilities localized to global resemblances. This paper aims to describe: Entrepreneurship Learning Patterns that must be done in order to change the direction, perceptions, and attitudes of students in the process of learning at the Tarbiyah College of Raden Wijaya Mojokerto with regard to the Industrial Revolution 4.0 era. The results of the discussion can be summarized as follows: 1) Raden Wijaya Mojokerto Tarbiyah College of Sciences needs to strengthen Entrepreneurship Learning by changing the direction, perception, and attitudes of deepening global understanding in students' local space in the learning process by preparing themselves for the reality of 21st century work and developing deeper initiatives and self-direction skills, offering the right level of freedom to conduct self-direction and initiatives is a sustainable universal challenge for teachers and parents. 2) Change in perception depends on the ability of the teacher, when the teacher has a strong perception in relation to problem solving, critical thinking, cooperation, communication and creativity, they may appear to provide their students with a more open learning environment for student inquiry. and investigation and thus more conducive to positive student attitudes. 3) Raden Wijaya Mojokerto Tarbiyah College of Sciences needs to develop and implement a Program for Active Learning to strengthen the emphasis on non-academic programs with the aim of providing a more balanced and holistic educational foundation